(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
The Finite Element Method (FEM) and the other numerical strategies are viably actualized in linear and non-linear analysis of structures. Recently, a new displacement based on Applied Element Method (AEM) has been developed. It is applicable for static and dynamic for both linear and non-linear analysis of framed and continuum structures. In AEM, the structural member is partitioned into virtual elements connected through normal and shear springs representing stresses and strains of certain portion of structure. FEM assumes the material as continuous and can indicate highly stressed region of structure, however it is difficult to model separation of element unless crack location is known. The main advantage of AEM is that it can track the structural collapse behavior going through all phases of the application of loads. In the current research, the application of AEM is illustrated through a non-linear dynamic analysis. Progressive collapse simulation is conducted using Extreme Loading for Structures software (ELS), which follows the AEM. The experimental and analytical works carried by Park et al. [17 and 28] for 1/5 scaled 3 and 5 stories reinforced concrete structures are used for verification. Good matching between the experimental and numerical results has been obtained using ELS. Therefore, it can be confirmed that ELS is capable in simulating the structures’ behavior up to collapse. Furthermore, a study has been made to investigate the effect of considering the floor slabs on progressive collapse. The results show that considering slab in progressive collapse analysis of multistory buildings is important as neglecting the slabs’ contribution leads to incorrect simulation and uneconomic design.